The Moderation of Financial Performance in the Phenomenon of Firm Value - Soediro, Achmad; Kusumawardani, Media; Dwinanda, Fadhilah; Farhan, Muhammad (STIE Malangkucecwara, 2025)
The research is conducted to investigate how ISR, the presence of the IBC, and the CS affect the value of firm, considering FP as a moderating element. It indicates that ISR has a notably favorable impact on a company's value. Nevertheless, IBC and CS do not exert any significant impact on FV. Additionally, concerning moderation effects, Social and Environmental Disclosure (SED) reduces the positive ISR impact on the value of firm but has no bearing on the influence of IBC on FV. Conversely, SED actually strengthens the impact of CS on FV. Furthermore, ROA enhances the positive ISR effect on FV while diminishing the impact of IBC on FV. Nonetheless, ROA has not effectively moderated the effect of CS on the value of firm.